2018
DOI: 10.1111/gcb.14279
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal remote sensing of ecosystem change and causation across Alaska

Abstract: Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio-environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high-latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 127 publications
(184 reference statements)
3
86
0
Order By: Relevance
“…This is similar to the amount of change detected in the Arctic Network of National Parks, located to the west of the Refuge, where a similar methodology found 24% of 206 systematically distributed plots showed change between 1975-1985 and 2008-2010 [27]. Our finding also compare to an Alaska-wide analysis, in which Pastick et al [37] found 14% of the landscape had undergone change from 1984 to 2015, based on an analysis of spectral trends in Landsat imagery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is similar to the amount of change detected in the Arctic Network of National Parks, located to the west of the Refuge, where a similar methodology found 24% of 206 systematically distributed plots showed change between 1975-1985 and 2008-2010 [27]. Our finding also compare to an Alaska-wide analysis, in which Pastick et al [37] found 14% of the landscape had undergone change from 1984 to 2015, based on an analysis of spectral trends in Landsat imagery.…”
Section: Discussionsupporting
confidence: 89%
“…The dataset developed by this study has been used for projecting future changes across a broader region of northern Alaska using state-transition modeling [62] and for landscape change analysis using satellite remote sensing and decision-tree modeling [37]. We found that environmental variables were very useful in explaining variations in change types across the region and can be incorporated into other studies.…”
Section: Limitations and Applications Of Remotely Sensed Changementioning
confidence: 95%
“…) and cover (Pastick et al. ) in areas already classified as Shrub (i.e., that did not undergo a coarse land‐cover transition). Indeed, it seems likely that increases in the stature and biomass of existing individuals and clones would be a common initial response to ameliorating conditions in systems such as ours, which are dominated by long‐lived perennial species (e.g., Walker et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Swanson , Pastick et al. ), the variation in shrub and tree expansion is not well understood and is spatially variable, representing a complex interplay between climate and soil conditions (Brenning , Tape et al. , Roland et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation